Measuring sentence similarity from different aspects - Lin Li; Xia Hu; Bi-Yun Hu; Jun Wang; Yi-Ming Zhou (2009 International Conference on Machine Learning and Cybernetics, 2009)
The paper proposes to determine sentence similarities from different aspects. Based on the information people get from a sentence, objects-specified similarity, objects-property similarity, objects-behavior similarity and overall similarity are defined to determine sentence similarities from four aspects. Experiments show that the proposed method makes the sentence similarity comparison more exactly and give out a more reasonable result, which is similar to the people's comprehension to the meanings of the sentences.